Parametric study of the effect of phase anisotropy on the micromechanical behaviour of dentin-adhesive interfaces - Spencer, Paulette; Wang, Yong; Misra, Anil S.; Katz, J. Lawrence; Marangos, Orestes (My University, 2005)
A finite element (FE) model has been developed based upon the recently measured microscale morphological, chemical and mechanical properties of dentin-adhesive (d-a) interfaces using confocal Raman microspectroscopy and scanning acoustic microscopy (SAM). The results computed from this FE model indicated that the stress distributions and concentrations are affected by the micro-scale elastic properties of various phases composing the d-a interface. However, these computations were performed assuming isotropic material properties for the d-a interface. The d-a interface components, such as the peritubular and intertubular dentin, the partially demineralized dentin and the so-called 'hybrid layer' adhesive-collagen composite, are probably anisotropic. In this paper, the FE model is extended to account for the probable anisotropic properties of these d-a interface phases. A parametric study is performed to study the effect of anisotropy on the micromechanical stress distributions in the hybrid layer and the peritubular dentin phases of the d-a interface. It is found that the anisotropy of the phases affects the region and extent of stress concentration as well as the location of the maximum stress concentrations. Thus, the anisotropy of the phases could effect the probable location of failure initiation, whether in the peritubular region or in the hybrid layer. © 2005 The Royal Society.
Keywords: Anisotropy; Dentin adhesive interface; Finite element analysis; Micromechanics; Stress distributions